Allergic Contact Dermatitis with Diffuse Erythematous Reaction from Diisopropanolamine in a Compress - Tomoko Rind; Naoki Oiso; Ayaka Hirao; Akira Kawada (Karger Publishers, 2010)
Compresses containing a nonsteroidal antiinflammatory drug (NSAID) are commonly used in Japan. However, this treatment may induce both allergic and photoallergic contact dermatitis from the NSAIDs and their ingredients. Here, we describe a case of allergic contact dermatitis with diffuse erythematous reaction due to diisopropanolamine in the applied compress. The absorption of diisopropanolamine might have been enhanced by the occlusive condition.